The role of sleep deprivation due to frequent breastfeeding in the development of post-partum depression: a cross-sectional study - Ahmad, Husnain; Yousaf, Sheraz; Sardar, Hassan; Nadir, Fizzah; Raza, Rimsha (Journal of the Pakistan Medical Association, 2025)
Objective: To identify the prevalence of and risk factors for postpartum depression associated with a lack of sleep due to breastfeeding. Method: From June to December 2023, a cross-sectional study was carried out in the psychiatric units of Sahiwal Teaching Hospital and Allied Hospital Faisalabad, two tertiary care facilities in Pakistan. Women between the ages of 18 and 40 who were primigravidas during the first six months after giving birth were included in the study. The Edinburgh Postnatal Depression Scale (EPDS) and the Pittsburgh Sleep Quality Index (PSQI) were used to gather data, and SPSS version 30 was used for analysis. Results: Out of 200 participants, 55 (27%) reported sleep disturbances (PSQI > 5), of whom 25 (12.5%) also exhibited symptoms of postpartum depression (EPDS > 10). The mean self-reported total sleep duration, including all naps within a 24-hour period, was 5 + 1.3 hours, with an average sleep efficiency of 60 + 14%. A statistically significant association was observed between sleep disturbances and postpartum depression (X² = 40.125, p < 0.0001), indicating that participants with poor sleep quality were significantly more likely to experience depressive symptoms. Conclusion: Nursing-related sleep deprivation was identified as a cause of postpartum depression. Improving sleep quality may aid in the reduction of postpartum depression. Key Words: Postpartum depression, Sleep deprivation, Breastfeeding, Pittsburgh Sleep Quality Index, Edinburgh Postnatal Depression Scale, Maternal health, Sleep quality, Nursing, Psychological adjustment, Risk factors.